2016
DOI: 10.1016/j.bjane.2014.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Combined spinal–epidural analgesia in labour: its effects on delivery outcome

Abstract: There were no significant differences in the duration of labour, rate of instrumental vaginal delivery and emergency cesarean section, and neonatal outcome in parturients who received compared to those who did not receive CSE for labour analgesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 20 publications
0
20
1
4
Order By: Relevance
“…Previous studies have contemplated that the degree of motor block achieved by an epidural analgesia may result in a prolonged labour and therefore increase the rates of a CS delivery [19]. Other studies [17, 20] however have demonstrated that epidural analgesia per se is unlikely to affect the chances of a normal delivery and there are many other factors that may contribute to a CS delivery such as the increased birthweight [17]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have contemplated that the degree of motor block achieved by an epidural analgesia may result in a prolonged labour and therefore increase the rates of a CS delivery [19]. Other studies [17, 20] however have demonstrated that epidural analgesia per se is unlikely to affect the chances of a normal delivery and there are many other factors that may contribute to a CS delivery such as the increased birthweight [17]. …”
Section: Discussionmentioning
confidence: 99%
“…Second, our electronic database does not have a mandatory field for recording the epidural regimen that was used. There is literature evidence showing that different epidural analgesia formulas exhibit a different effect on the course of labour and the delivery outcome [19, 20]. The main strength of our study includes its large sample size with inclusion of women who were primigravidae and under 40 years of age and had a normal BMI at booking in order to account for the significant confounding factors of parity [5], age [6], and body mass index (BMI) [7] on the success of induced labour.…”
Section: Discussionmentioning
confidence: 99%
“…There is literature evidence showing that different epidural analgesia formulas exhibit a different effect on the course of labour and the delivery outcome. 8,10 Epidural anesthesia allows a gradual onset of block with avoidance of hypotension by intermittent fluid bolus. Keeping the underlying pathophysiology in view, we aimed to maintain hemodynamic stability by maintaining an optimum systemic vascular resistance, preload, heart rate, sinus rhythm and decrease in pulmonary vascular resistance.…”
Section: Discussionmentioning
confidence: 99%
“…7). In neueren Arbeiten werden für epidurale Injektionen meist nur noch Konzentrationen von 0,0625-0,125 % für Bupivacain und 0,0625-0,15 % für Ropivacain eingesetzt [9,13,14].…”
Section: Low-dose-mixtures In Der Forschungunclassified
“…Die Annahme, dass hierfür eine zu frühe neuraxiale Blockade verant-wortlich ist (Muttermund < 4 cm), wurde mittlerweile eindrucksvoll widerlegt [32,33]. In einem Direktvergleich zwischen CSE und Nicht-CSE (Lachgasanalgesie + intramuskuläres Pethidin und Promethazin) ergab sich ebenfalls kein Unterschied im Entbindungsmodus und fetalem Ergebnis; die Dauer der Geburt war in beiden Gruppen gleich [13].…”
Section: Auswirkungen Auf Entbindungsmodus Und Apgar-werteunclassified